Pengaruh Gaya Kepemimpinan Transformasional Dan Lingkungan Kerja terhadap Kinerja Pegawai Baznaz Kota Samarinda - Lia Silpia; Mursyid Mursyid; Anwaril Hamidy; Nur Rahmatullah (Borneo Islamic Finance and Economics Journal, 2022)
Human resources are the most important asset for the organization, because they have a very important role in carrying out their duties both for improving performance and facing demands in work. Because of the conditions that will require the leader's skills in managing any changes that will occur and the facilities required must be good, so the author wants to know about the influence of a leader with a transformational leadership style, the influence of the existing work environment, and the results of the performance of his employees at BAZNAS Samarinda City. . This study aims to determine the effect of transformational leadership style and work environment on the performance of BAZNAS employees in Samarinda. The research method used is quantitative research with causal research, with a population of 11 respondents using a saturated sampling technique (census). Meanwhile, the data collection technique used is the Questionnaire. The results of this study indicate that Transformational Leadership Style has a significant effect on employee performance, the work environment partially does not significantly affect employee performance and simultaneously Transformational Leadership Style and work environment affect employee performance with a coefficient of determination R square of 0.970 or equal to 97 %. Keywords : Transformational Leadership Style, Work Environment, Performance.